Semantic Preview Benefit of Tibetan-Chinese Bilinguals during Chinese Reading. Issue 1 (2nd January 2023) - Xiao, Xue-Zhen; Jia, Gaoding; Wang, Aiping
ABSTRACT: When reading Chinese, skilled native readers regularly gain a preview benefit (PB) when the parafoveal word is orthographically or semantically related to the target word. Evidence shows that non-native, beginning Chinese readers can obtain an orthographic PB during Chinese reading, which indicates the parafoveal processing of low-level visual information. However, whether non-native Chinese readers who are more proficient in Chinese can make use of high-level parafoveal information remains unknown. Therefore, this study examined parafoveal processing during Chinese reading among Tibetan-Chinese bilinguals with high Chinese proficiency and compared their PB effects with those from native Chinese readers. Tibetan-Chinese bilinguals demonstrated both orthographic and semantic PB but did not show phonological PB and only differed from native Chinese in the identical PB when preview characters were identical to the targets. These findings demonstrate that non-native Chinese readers can extract semantic information from parafoveal preview during Chinese reading and highlight the modulation of parafoveal processing efficiency by reading proficiency. The results are in line with the direct route to access the mental lexicon of visual Chinese characters among non-native Chinese speakers.